Non-alcoholic Fatty Liver Disease in Children: An emerging Public health problem in India - Rastogi, Aayushi; Kapil, Umesh (Indian Journal of Community Health, 2020)
NAFLD was earlier believed to be the disease of adults only however in 1983, the existence of this disease was seen in paediatric population. Nearly four decades have passed since the first description of the Paediatric NAFLD (P-NAFLD), yet it is one of the areas which is given least priority in the country. The P-NAFLD is reversible and can be prevented by lifestyle and behaviour modification and hence there is a need to this review highlights the importance of P-NAFLD in the country and need for formulating strategies for prevention and control of P-NAFLD in the country. All published articles in the MEDLINE database on P-NAFLD in India were included. The important findings were summarized and critically analysed. The existing review suggests, the prevalence of P-NAFLD is uncertain in the country. NAFLD is a phenotypic product of complex interaction of heredity (nature) and environment (nurture). This review summarizes the importance of P-NAFLD in India and discusses the predisposition of these risk factors in Indian children. Further population-based studies on prevalence and incidence are required on general paediatric population to quantify the magnitude of the disease in India for better management of the condition.